2010
DOI: 10.1080/08911762.2010.504523
|View full text |Cite
|
Sign up to set email alerts
|

English in Product Advertisements in Non-English-Speaking Countries in Western Europe: Product Image and Comprehension of the Text

Abstract: Although English has been shown to be the most frequently used foreign language in product advertisements in countries where it is not the native language, little is known about its effects. This article examines the response to advertisements in English compared to the response to the same ad in the local language in Western Europe on members of the target group for which the ad was intended: 715 young, highly educated female consumers. The use of English in a product ad does not appear to have any impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 51 publications
(58 reference statements)
2
43
0
1
Order By: Relevance
“…Puntoni, De Langhe, and van Osselaer (2009) show also that consumers perceive messages expressed in the local language as more emotional than messages expressed in English. Finally, Gerritsen et al (2010) study the effects of using English in product advertising in France, Holland, Belgium, Spain, and Germany. They report that the target groups did not understand 40% of the sentences used in six paper ads.…”
Section: Language Differences In Advertisementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Puntoni, De Langhe, and van Osselaer (2009) show also that consumers perceive messages expressed in the local language as more emotional than messages expressed in English. Finally, Gerritsen et al (2010) study the effects of using English in product advertising in France, Holland, Belgium, Spain, and Germany. They report that the target groups did not understand 40% of the sentences used in six paper ads.…”
Section: Language Differences In Advertisementsmentioning
confidence: 99%
“…Among the many different aspects of television advertising that may influence consumer response, relatively little attention has been paid to the impact of language choice (Gerritsen et al 2010). Although TV advertising is pervasive throughout the world and multinational companies use many of the same adverts in different countries, few studies have considered the effects on consumers of using a foreign language in a TV advert instead of a local one.…”
Section: Introductionmentioning
confidence: 99%
“…In this pretest, 28 respondents (50% female; age M = 30.56 years, SD = 14.18; education ranged from primary school to university) indicated their luxury perception and estimated price for the following eight products: automobile, bread, chocolate, fruit, perfume, smartphone, detergent, and vodka (based on Krishna and Ahluwalia 2008;Gerritsen et al 2010;Hornikx, van Meurs, and de Boer 2010). Respondents rated the products on three 7-point semantic differentials: "expensive-cheap" (Gerritsen et al 2010); "a luxury product-a necessity product"; "luxury for everyone-necessity for everyone" (Krishna and Ahluwalia 2008). The scores showed that chocolate was regarded as a product that was positioned between a necessity and a luxury product (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Since English is a nonnative language for consumers in countries such as the Netherlands, English in advertising may not always be comprehended. In fact, Gerritsen et al (2010) found that 39 percent of English phrases in print medium ads were not described correctly by participants from Belgium, France, Germany, the Netherlands, and Spain. The question, therefore, is to what extent comprehension of English in advertisements is important in persuading consumers.…”
mentioning
confidence: 99%
“…However, as far as is known, it has not been experimentally investigated whether the use of English in advertising in non-English-speaking countries functions as a peripheral cue, and thus whether its effect depends on the thoroughness with which the advertising message is processed. Processing conditions have not been taken into account at all in extant experimental research into the effect of the use of English or Dutch in product advertising on Dutch participants' attitude to the product and behavioural intention (Dasselaar, Van Meurs, Le Pair, & Korzilius, 2005;Gerritsen et al, 2007;Gerritsen et al, 2010;Hornikx, Van Meurs, De Boer, 2010;Smakman, Korzilius, Van Meurs, & Van Neerven, 2009), nor in research into the effect of English or Dutch in recruitment advertising on Dutch participants' attitudes to the job and the organization and their job pursuit intentions (Renkema, Vallen, & Hoeken, 2001;Van Meurs et al, 2004;Van Meurs, Korzilius, & Den Hollander, 2006a).…”
Section: Introductionmentioning
confidence: 99%